Pregunta
upstudy study bank question image url

2. Solve the simultaneous equations \( 3 x+4 y=23 \) \( 2 x-4 y=2 \)

Ask by Alexander Pritchard. in South Africa
Mar 12,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( x=5 \) and \( y=2 \).

Solución

Solve the system of equations \( 3x+4y=23;2x-4y=2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+4y=23\\2x-4y=2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{23-4y}{3}\\2x-4y=2\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2\times \frac{23-4y}{3}-4y=2\) - step3: Simplify: \(\frac{2\left(23-4y\right)}{3}-4y=2\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{2\left(23-4y\right)}{3}-4y\right)\times 3=2\times 3\) - step5: Simplify the equation: \(46-20y=6\) - step6: Move the constant to the right side: \(-20y=6-46\) - step7: Subtract the numbers: \(-20y=-40\) - step8: Change the signs: \(20y=40\) - step9: Divide both sides: \(\frac{20y}{20}=\frac{40}{20}\) - step10: Divide the numbers: \(y=2\) - step11: Substitute the value of \(y:\) \(x=\frac{23-4\times 2}{3}\) - step12: Calculate: \(x=5\) - step13: Calculate: \(\left\{ \begin{array}{l}x=5\\y=2\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=5\\y=2\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(5,2\right)\) The solution to the simultaneous equations \(3x+4y=23\) and \(2x-4y=2\) is \(x=5\) and \(y=2\).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the simultaneous equations, we can use the substitution or elimination method. Let's use the elimination method here. First, we can add both equations to eliminate \(y\): 1. \(3x + 4y = 23\) 2. \(2x - 4y = 2\) Adding these, we get: \((3x + 4y) + (2x - 4y) = 23 + 2\) This simplifies to: \(5x = 25\) Now, divide both sides by 5: \(x = 5\) Next, substitute \(x = 5\) back into one of the original equations to find \(y\). We'll use the first equation: \(3(5) + 4y = 23\) This simplifies to: \(15 + 4y = 23\) Now, subtract 15 from both sides: \(4y = 8\) Dividing by 4, we find: \(y = 2\) Thus, the solution to the simultaneous equations is \(x = 5\) and \(y = 2\).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad